Pegaso Peru: An Overdue Project (A) and (B). Issue 1 (May 2014) - Tsuja, Peter Yamakawa; Rees, Gareth H; Tuesta, Julio Quispe; Marengo, José Carrión; Escobar, Kenny Luis; Guevara Aquije, Julio
Brunella Noli, General Manager of a Peruvian consulting firm (Pegaso Peru), reviews the history of a troubled IT project for client Casa Master Center (CMC). The project is 11 months overdue, and CMC is an increasingly unhappy client. Noli's review, which starts with the sale and recounts the project's scope, contract and implementation, uncovers a series of problems. Noli seeks to resolve these issues without incurring additional costs. She worries that the relationship with the client is rapidly deteriorating and she fears that this will damage Pegaso's reputation. A second one-page Case B recounts what happened next. This case is based on actual events in real organizations. The identities of the parties involved have been changed, along with other key information, to preserve anonymity.